DETECTION OF LUMPY SKIN DISEASE VIRUS GENOME IN FIELD SAMPLES COLLECTED FROM CATTLE IN THE RUSSIAN FEDERATION - A. V. Kononov; A. V. Sprygin; S. V. Kononova; A. A. Nesterov; P. V. Prutnikov; Ye. Ye. Artyukhova; Ye. S. Kostrova; I. N. Shumilova (Ветеринария сегодня)
Results of laboratory tests of pathological and biological material samples for lumpy skin disease virus genome with the FGBI “ARRIAH” lumpy skin disease real-time PCR test system are presented. Samples were collected from cattle in 16 regions of the Russian Federation in 2016–2017. A total of 848 stabilized blood, serum, skin (nodule) scrape, nasal washing samples were tested. In the process of antemortem diagnosis lumpy skin disease virus genome was detected in nasal washings (29.2%), serum (19.5%) and stabilized blood (24.4%). Lumpy skin disease virus genome was detected in skin lesion samples (77.7% of cases) during postmortem diagnosis. No lumpy skin disease virus genome was detected in trachea, spleen and aborted fetus samples. Thus, in case of lumpy skin disease suspicion serum and nasal washing samples shall be tested first for antemortem diagnosis, while nodules (lumps) shall be primarily tested for postmortem diagnosis.